PENGARUH LINGKUNGAN KELUARGA DAN PENGALAMAN PRAKTIK KERJA INDUSTRI TERHADAP MINAT BERWIRAUSAHA SISWA SMK - Farida Fadlilah; Sri Wahyuni; Leny Noviani (Department of Economics Education, Universitas Sebelas Maret, 2018)
The objective of research were to find out the effect of family environment and industrial working practice experience towards entrepreneurship interest in XI grade. The method used in this study was descriptive quantitative method with survey . The sample in this study were 151 students XII grade in SMK Batik 1 Surakarta academic year 2015/2016. The data collection techniques used questionnaires. The data were analyzed by using multiple regression analysis. The results showed that there was a significant positive effect of family environment and industrial working practice experience simultaneously towards entrepreneurship interest. The magnitude of the effect of family environment and industrial working practice experience towards entrepreneurship interest simultaneously obtained from the calculation of the R- square of 41,5%.